Public Relations Vis-A-Vis attitudes and Perceptions of users of services - A synthesis for tourism promotion marketing - Kamra, Mansi (Atna Journal of Tourism Studies, 2021)
The paper begins by spelling out the relevance of service sector in the contemporary scenario,. It then dwells a little on the meaning and concept of public relations besides highlighting its significance in the corporate world. The direction and orientation of consumer behaviour in Tourism is them brought out and examined. A specific section is devoted to tourism and promotion marketing. The paper focuses specially on the aspect of public relations in the tourism industry. The paper goes on to bring out an interaction between public relations and travel intermediaries. It endeavours to draw attention to the role of public relations as a promotion marketing tool. Finally, the study round off by inferring that in tourism business, public relations as a management function has so far not been incorporated to the extent it should have been. Using ‘advertising’ as a part of the marketing function is conceptually different from using ‘public relations’ to create productive relationship. Marketing and advertising in tourism or intangibles/services are generally aggressive in nature’ public relations on the other hand, is a suitable human activity. It is in fact on extension of international relationships and therefore more friendly as well as productive